Non-infectious immune complexes downregulate the production of interferons and tumor necrosis factor-α in primary porcine alveolar macrophages in vitro - Zhang, Liujun; Feng, Xing; Chen, Weizhen; Wang, Bo; He, Shaojun; Fan, Hongjie; Liu, Deyi (Frontiers in Veterinary Science, 2024)
Porcine reproductive and respiratory syndrome (PRRS) caused by the PRRS virus (PRRSV) has been harming the pig industry worldwide for nearly 40 years. Although scientific researchers have made substantial efforts to explore PRRSV pathogenesis, the immune factors influencing PRRSV infection still need to be better understood. Infectious virus-antibody immune complexes (ICs) formed by PRRSV and sub-or non-neutralizing antibodies specific for PRRSV may significantly promote the development of PRRS by enhancing PRRSV replication through antibody-dependent enhancement.However, nothing is known about whether PRRSV infection is affected by non-infectious ICs (NICs) formed by non-pathogenic/infectious antigens and corresponding specific antibodies. Here, we found that PRRSV significantly induced the transcripts and proteins of interferon-α (IFN-α), IFN-β, IFN-γ, IFN-λ1, and tumor necrosis factor-α (TNF-α) in vitro primary porcine alveolar macrophages (PAMs) in the early stage of infection. Our results showed that NICs formed by rabbit-negative IgG (RNI) and pig anti-RNI specific IgG significantly reduced the transcripts and proteins of IFN-α, IFN-β, IFN-γ, IFN-λ1, and TNF-α in vitro PAMs and significantly elevated the transcripts and proteins of interleukine-10 (IL-10) and transforming growth factor-β1 (TGF-β1) in vitro PAMs. NICs-mediated PRRSV infection showed that NICs not only significantly decreased the induction of IFN-α, IFN-β, IFN-γ, IFN-λ1, and TNF-α by PRRSV but also significantly increased the induction of IL-10 and TGF-β1 by PRRSV and considerably enhanced PRRSV replication in vitro PAMs. Our data suggested that NICs could downregulate the production of antiviral cytokines (IFN-α/β/γ/λ1 and TNF-α) during PRRSV infection in vitro and facilitated PRRSV proliferation in its host cells by inhibiting innate antiviral immune response. This study elucidated one novel immune response to PRRSV infection, which would enhance our understanding of the pathogenesis of PRRSV.